Searching for the muon decay to three electrons with the Mu3e experiment - Martin Perez, Cristina; Vigani, Luigi (Universe, 2021)
Mu3e is a dedicated experiment designed to find or exclude the charged lepton flavor violating μ→ eee decay at branching fractions above 10−16. The search is pursued in two operational phases: Phase I uses an existing beamline at the Paul Scherrer Institute (PSI), targeting a single event sensitivity of 2·10−15, while the ultimate sensitivity is reached in Phase II using a high intensity muon beamline under study at PSI. As the μ→ eee decay is heavily suppressed in the Standard Model of particle physics, the observation of such a signal would be an unambiguous indication of the existence of new physics. Achieving the desired sensitivity requires a high rate of muons (108 stopped muons per second) along with a detector with large kinematic acceptance and efficiency, able to reconstruct the low momentum of the decay electrons and positrons. To achieve this goal, the Mu3e experiment is mounted with an ultra thin tracking detector based on monolithic active pixel sensors for excellent momentum and vertex resolution, combined with scintillating fibers and tiles for precise timing measurements.
Gesehen am 22.12.2021
This article belongs to the special issue "Charged lepton flavor violation"